The Use of Tiktok Application to Improve the Second Grade Students’ Speaking Skills at SMA Negeri 3 Takalar - Fortuna, Nursharikha Aghniya; Noni, Nurdin; Munir, Munir (Journal of Excellence in English Language Education, 2024)
This study was conducted to determine whether using the TikTok application increases students’ speaking skills in English. The method used was quantitative research with a pre-experimental one-group pre-test-post-test design. The population of this study was 11th-grade students from SMAN 3 Takalar in the academic year 2023/2024, and the sample of this study was class XI with 36 students. This study uses a cluster random sampling technique. The research instrument used a speaking test with the topic of opinions and thoughts. This research is based on data processing, with the average score from the pre-test (37.97) < the average score from the post-test (63.36), significance value .000 < α (.05), and t-value (12.360) > t-table (2.101). The results of the study indicate that the speaking skills of 11th-grade students at SMAN 3 Bone improved after receiving several treatments. In conclusion, using the TikTok application increases students’ English-speaking skills.